Pelaksanaan Pembelajaran Dinul Islam KPM-DRI di Gampoeng Lubok Batee, Ingin Jaya, Aceh Besar - Lufiana, Aina Firdha; Amiruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
As the consequences of Covid-19 pandemic, children’s interest in learning is decreasing. This study was conducted in gampoeng Lubok Batee which aims to see the influence of the implementation Dinul Islam learning during Ramadhan on children’s achievement. The study uses the observation method as the tool in collecting the data. Observation allows the researcher to watch peoples' behaviors and interactions directly, or watch for the results of behaviors or interactions. The researcher implement the program of KPM-DRI in conducting academic and non-academic coaching in order to explore self-potential and improve children's achievement.